Epithelial folliculin enhances airway inflammation in aspirin‐exacerbated respiratory disease - Trinh, Hoang Kim Tu; Pham, Duy Le; Choi, Youngwoo; Kim, Hyun‐Mi; Kim, Seung‐Hyun; Park, Hae‐Sim (Clinical and experimental allergy, 2018)
Background Clinical features of aspirin‐exacerbated respiratory disease (AERD) are characterized by overproduction of cysteinyl leukotrienes (LT) and eosinophil activation, in which epithelial cells contribute to eosinophilic airway inflammation. Folliculin (FLCN) helps maintain the integrity of epithelial barrier, but little is known about FLCN in AERD. Objective We investigated the role of FLCN in the pathogenic mechanisms of AERD. Methods We recruited 178 subjects with AERD, 276 subjects with aspirin‐tolerant asthma (ATA) and 71 normal healthy controls (NC) at Ajou Medical Center. Levels of FLCN and interleukin (IL)‐8 in sera and supernatants were measured by ELISA. Peripheral blood eosinophils isolated from asthmatic patients were cocultured with human airway epithelial cells (HAECs) pretreated with LTE4, dexamethasone and montelukast. The intracellular expressions of FLCN, tight (TJ) (occludins, claudin‐1) and adherens (AJ) junctions (E‐cadherin) were analysed by Western blotting. shRNA was used to down‐regulate FLCN (shFLCN) in HAECs. Results Serum FLCN levels were significantly higher in AERD group than in ATA and NC groups (all P < 0.001). The cut‐off value of 56.6 pg/mL was used to define the high FLCN phenotype (highFLCN). Asthmatic patients with highFLCN were associated with increased airway hyperresponsiveness to methacholine (P = 0.015). The serum FLCN level could discriminate AERD group from NC group with 82% sensitivity (AUC = 0.793, P < 0.001). When HAECs were exposed to LTE4, FLCN release was increased significantly (P < 0.05), which were amplified along with disruption of TJ and AJ expressions when HAECs were cocultured with eosinophils and LTE4 (all P < 0.05); these effects were suppressed by dexamethasone and montelukast. FLCN knockdown reduced IL‐8 release and occludin expression from shFLCN HAECs. Conclusions Our findings suggest that high LT and airway eosinophilia increased FLCN release from HAECs, which enhance epithelial activation and disruption. Modulation of FLCN may be a potential target for AERD.